Direct Acting Oral Anticoagulant vs. Warfarin in the Prevention of Thromboembolism in Patients With Non-valvular Atrial Fibrillation With Valvular Heart Disease—A Systematic Review and Meta-Analysis - Martha, Januar Wibawa; Pranata, Raymond; Raffaelo, Wilson Matthew; Wibowo, Arief; Akbar, Mohammad Rizki (Frontiers in Cardiovascular Medicine, 2021)
Purpose Uncertainty surrounds which anticoagulant to be used in non-valvular atrial fibrillation (AF) with valvular heart disease. This systematic review and meta-analysis aimed to assess the efficacy and safety of direct acting oral anticoagulants (DOACs) compared to warfarin in patients with non-valvular AF with valvular heart disease. Methods We performed a comprehensive literature search using PubMed, Scopus, Embase, and Clinicaltrials.gov from the inception of databases up until 02 August 2021, the search was updated and finalized on 17 October 2021. The intervention group were DOACs and the control group was warfarin. The primary outcome was systemic embolism and stroke (SSE), and. the secondary outcome was major bleeding and intracranial haemorrhage. The pooled effect estimate was reported as hazard ratio (HR) and odds ratio (OR). Results There were 21,185 patients from seven studies included in this systematic review and meta-analysis. Stroke and systemic embolism were lower in patients receiving DOACs (HR 0.76 [95%CI 0.67, 0.87], p<0.001; I2: 5%) compared to warfarin. Subgroup analysis on RCTs showed significant reduction of SSE in DOACs group (HR 0.73 [95%CI 0.60, 0.89], p=0.002; I2: 16%). There was no significant difference in terms of major bleeding (HR 0.89 [95%CI 0.75, 1.05], p=0.18; I2: 69%). Intracranial haemorrhage (HR 0.42 [95%CI 0.22, 0.80], p=0.008; I2: 73%) were lower in the DOAC group. Conclusion This meta-analysis indicates that DOACs was associated with lower risk of SSE and intracranial haemorrhage compared to patients receiving warfarin. There was no significant difference between the two groups in terms of major bleeding.